Should carbon taxes be pre-announced? On irreversible investment, real options and carbon taxes - Sweder van Wijnbergen (Tinbergen Institute, 2025)
Climate change and its two-way relation with economic activity is stochastic and so is therefore the optimal tax internalizing the climate externality. But with capital irreversibility a stochastic time path for carbon prices slows down the reallocation from brown to green sectors because waiting then acquires an option value. We show that it is optimal to pre-announce a time path for future carbon taxes, eliminating the option value of waiting at the cost of suboptimality of the pre-announced taxes at the time they apply. We analyse for how long carbon taxes should be pre-announced and which factors influence that timespan.
Keywords: G13; H2; Q51; Q54; 330; Carbon taxes; Social Cost of Carbon; Irreversible Capital; Real Options